Coronal replacement flap associated or not with platelet-rich fibrin membrane. Case report - Lázaro Sarduy Bermúdez; Olga Lidia Véliz Concepción; Felisa Veitia Cabarrocas (Acta Médica del Centro)
Introduction: with the use of traditional root coverage plastic techniques, some loss over time of the results achieved has been observed.The combination of regenerative materials such as platelet rich fibrin membrane with these surgical procedures can achieve tissue restoration that guarantees greater stability. Patient information: the case of a 30 year old male patient with a history of health, carrier of bilateral periodontal recessions in lower premolars is presented.The coronal replacement flap technique was performed in the right hemiarch and the same procedure was combined with the platelet-rich fibrin membrane on the left. Conclusions: superiority was demonstrated in relation to the procedure combined with the biomaterial, in terms of the percentage of root coverage and the stability of the results over time.